Political Communication Strategy Through Campaign Songs for Presidential and Vice-Presidential Candidates: An Analysis of the Song "OKAY GAS PRABOWO GIBRAN IS MOST FITTING" - Hari Eko Purwanto (Riwayat: Educational Journal of History and Humanities, 2024)
In modern politics, communication plays a pivotal role in influencing public perception of a candidate, especially through alternative media such as campaign songs. In Indonesia, the campaign song "Oke Gas Prabowo Gibran Paling Gas" has garnered attention for its effectiveness in conveying political messages through popular media. This study analyzes the campaign song using the Bandwagon Effect and The Communicative Function Model theories. It was found that the song successfully utilizes the concepts of conformity, interpersonal influence, and speaker status to persuade listeners to support the Prabowo and Gibran pair. This analysis reveals the importance of understanding political communication strategies in campaign songs to evaluate their effectiveness in achieving desired political goals. The campaign song effectively leverages social media and other platforms to capture the attention of the public, demonstrating the power of alternative media in modern politics. This research provides insights into the importance of understanding the political messages conveyed through alternative media such as campaign songs, and how they can influence public perception and support for a candidate.